Edukasi Penerapan Higiene dan Sanitasi pada Pelaku Usaha Makanan - Fea Firdani; Diva Khusnul Chotimah; Dwina Aulia Putri; Intan Sahara Kusuma; Muhammad Farhan Mantovani; Putri Aulia Azzahra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Along with the times, the human need for food served outside the home is increasing. So that individuals or companies provide more and more food products or businesses. Food safety is a significant thing to note. The behaviour of food handlers in processing and serving food has an essential role in protecting the food from contamination that can affect the health of the people who consume processed food products. This community service activity aims to provide education regarding hygiene and sanitation to food business actors. The training was conducted in October - November 2022 at 40 food businesses in Mata Air Village, South Padang District, Padang City. The implementation method started with field observations, which aim to determine the condition of the hygiene implementation of business actors, followed by providing education to business actors using poster media that contains the application of hygiene and sanitation in handling food and providing personal protective equipment for business actors that can be used to support the implementation of food handling hygiene in the place of business. The results of community service activities found that 97.5% of business premises did not meet hygiene and sanitation requirements. This inspection was seen from personal hygiene and sanitation in the place of business. Education on the application of personal hygiene and sanitation to business actors was carried out door to door to every restaurant business place by using posters containing information regarding the application of food handling hygiene and pasted on every food business place in the village to increase the knowledge of food handlers. Educational media and personal protective equipment are expected to increase restaurant business workers' knowledge and compliance in implementing personal hygiene in processing and serving food.